Development of Mobile QR Warehouse Management Apllication Based on Flutter and Firebase - Wairooy, Irma Kartika; Dillwyn, Ignatius; Yonathan, Kevin Putra; Lay, Andre (Bina Nusantara University, 2024)
Since the Covid-19 pandemic took place, the number of MSMEs (Micro, Small and Medium Enterprises) has increased. Running a good business requires good product management to minimize losses that occur due to errors in product management. This research aims to increase the efficiency of the product management process with the QR Scanner feature which can make things easier for MSME owners. This research was designed through various needs gathering steps which included literature studies, surveys and competitor analysis. The application design method used in the development of the QRHouse application will be based on the Object Oriented Programming (OOP) method which has many advantages ranging from its object-oriented nature so that the data structure will be more organized, and also has a variety of concepts that can be used for application development. Application development will also be supported through several UML diagrams consisting of use case diagram, use case description, activity diagram, class diagram, and sequence diagram. Each diagram will have a function that will make the application development process more organised and minimise the occurrence of errors and bugs during application development. The results of the research are an Android and iOS based mobile application called QRHouse. The testing methods used include User Acceptance Test, User Interface Survey, UI Evaluation with 8 Golden Rules, UX Evaluation with 5 Measurable Human Factors. The results of the research were achieved when the application developed succeeded in increasing efficiency in product stock management.